Bioequivalence studies of inhaled indacaterol maleate in healthy Chinese volunteers under gastrointestinal non-blocking or blocking with concomitant charcoal administration. (April 2020) - Zou, Chan; Yang, Qian; Yang, Shuang; Zhang, Xingfei; Yang, Xiaoyan; Huang, Zhijun; Pei, Qi; Huang, Jie; Yang, Guoping
Abstract: Background: Indacaterol is one of the long-acting beta2 -adrenergic agonists, referred as first-line monotherapy for Chronic obstructive pulmonary disease since 2011. Generic products are encouraged to benefit the large COPD patients in China, in which can provide more choices association with reduced cost and improve the quality of patient life. Objective: The three-part study consists of two independent cohorts of thirty-six subjects, aimed to evaluate the bioequivalence (BE) of two indacaterol formulations in gastrointestinal (GI) absorption charcoal-block or non-block conditions. One pilot study performed in six healthy subjects to determine the blocking effect of a new charcoal-based regimen on GI absorption after orally inhalation of indacaterol. Methods: Two BE studies were conducted with a randomized, open-label, 2-period crossover design in two independent 36-healthy-subject cohorts, equivalence in systemic and lung deposition was assessed after inhalation of a single dose of 150 μg indacaterol (test or reference formulation) alone or concomitant administration of charcoal. The charcoal-based regimen was improved by optimizing the dose and number of doses, and its blocking efficacy against GI absorption was assessed in a pilot study. Six healthy subjects received 9 g charcoal 10 min before, immediately after and 2 h after indacaterol (3 g/100 ml water × 3 times). Blood collected at predetermined time points up to 72 h. Plasma indacaterol concentrations were determined using HPLC-MS/MS. Pharmacokinetics parameters were calculated with non-compartment analysis. Equivalences were concluded if the 90% confidence interval (CI) for test: reference of Cmax and AUC0-t fell within the limits of 0.8–1.25. Results: Indacaterol was undetectable in plasma samples in pilot study. The T/R ratio of the geometric mean Cmax and AUC0-t was 109.9% (90% CI, 106.1–113.8%) and 104.8% (90% CI, 101.5–108.1%) for charcoal-block subjects and 105.4% (90% CI, 99.8% 111.3%), and 101.0% (90% CI, 97.7%–104.4%) for non-block subjects. No serious adverse events were reported. Conclusions: The results showed that 150 μg indacaterol (+/− 9 g charcoal) was well tolerated in all subjects. The two formulations are bioequivalent in terms of the rate and absorption both in charcoal-block and non-block conditions. The improved charcoal-based regimen demonstrated to be effective and fully blockade of GI absorption of indacaterol.